2020
DOI: 10.1051/0004-6361/201937121
|View full text |Cite
|
Sign up to set email alerts
|

Angular differential kernel phases

Abstract: Context. To reach its optimal performance, Fizeau interferometry requires that we work to resolve instrumental biases through calibration. One common technique used in high contrast imaging is angular differential imaging, which calibrates the point spread function and flux leakage using a rotation in the focal plane. Aims. Our aim is to experimentally demonstrate and validate the efficacy of an angular differential kernel-phase approach, a new method for self-calibrating interferometric observables that opera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Furthermore, the reduced χ 2 of our binary model fits is larger than one, meaning that we are underestimating the errors. This is in agreement with previous studies that have shown that the kernel phase technique is dominated by systematic errors, usually yielding a reduced χ 2 between ∼ 1-10 ( Martinache et al 2020;Laugier et al 2020;Kammerer et al 2019;Ireland 2013).…”
Section: Binary Model Fitssupporting
confidence: 93%
“…Furthermore, the reduced χ 2 of our binary model fits is larger than one, meaning that we are underestimating the errors. This is in agreement with previous studies that have shown that the kernel phase technique is dominated by systematic errors, usually yielding a reduced χ 2 between ∼ 1-10 ( Martinache et al 2020;Laugier et al 2020;Kammerer et al 2019;Ireland 2013).…”
Section: Binary Model Fitssupporting
confidence: 93%
“…Later, Kammerer et al (2019) and Wallace et al (2020) conducted the first KPI surveys for young self-luminous companions at small angular separations which are inaccessible with classical coronagraphy techniques. At the same time, Laugier et al (2019) developed methods to apply the KPI technique to saturated images and also introduced angular differential kernels (Laugier et al 2020) which take advantage of the angular diversity of ground-based pupil tracking mode data to selfcalibrate kernel phase observables. The CLEARP pupil mask enables full pupil images using AMI filters, target acquisition, and fast readout subarray.…”
Section: Kernel Phase Interferometrymentioning
confidence: 99%
“…This is likewise an issue where detector nonlinearity and saturation significantly distort the PSF. While the analytic series expansion is no longer applicable in these regimes, using matrix Fourier transforms and skipping saturated pixels or pixels inside the coronagraphic inner working angle has shown promise for pushing kernel phase beyond its conventional limitations (Laugier & Martinache 2019), as have generalizations that exploit angular differential imaging for a further level of calibration (Laugier et al 2020).…”
Section: Complex Optical Systems: Nullers and Coronagraphsmentioning
confidence: 99%